2011
DOI: 10.1017/s0007114511005496
|View full text |Cite
|
Sign up to set email alerts
|

Effects of grape seed extract supplementation on exercise-induced oxidative stress in rats

Abstract: The aim of the present study was to investigate the effects of grape seed extract (GSE) supplementation on exercise performance and oxidative stress in acutely and chronically exercised rats. A total of sixty-four male rats were used in the study. Rats were divided into six groups: control, chronic exercise control, acute exercise control (AEC), GSE-supplemented control, GSE-supplemented chronic exercise and GSE-supplemented acute exercise groups. Chronic exercise consisted of treadmill running at 25 m/min, 45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 54 publications
2
32
0
1
Order By: Relevance
“…Results of our study suggest that Ex may enhance lipid peroxidation and reduce the oxidative damage of proteins and DNA 23. Reduced oxidative stress results from an enhanced antioxidant defense system 24,25. Chronic Ex reduces oxidative stress by upregulating the activity of antioxidant enzymes 26.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Results of our study suggest that Ex may enhance lipid peroxidation and reduce the oxidative damage of proteins and DNA 23. Reduced oxidative stress results from an enhanced antioxidant defense system 24,25. Chronic Ex reduces oxidative stress by upregulating the activity of antioxidant enzymes 26.…”
Section: Discussionmentioning
confidence: 78%
“…Chronic Ex reduces oxidative stress by upregulating the activity of antioxidant enzymes 26. Belviranli et al25 have reported that plasma MDA levels were lowered in chronically exercised groups compared to controls, as well as by an antioxidant (grape seed extract) supplementation. They also reported the plasma activities of SOD, an antioxidant defense for superoxide radicals that catalyzes the dismutation of superoxide and the formation of H 2 O 2 and GPx.…”
Section: Discussionmentioning
confidence: 99%
“…There was no difference for the amount of water and diet consumed among these groups. Similar dosages of GSE have been used in previous studies [22,23]. GSE used in this study is a commercial GSE product (Gravinol-S) purchased from OptiPure Chemco Industries Inc. (Los Angeles, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Parallel to the studies on the benefi cial effects of exercise and its effects on oxidative stress investigations on the effects of dietary supplementation with antioxidants have been carried out by a number of authors. In the recent years special attention has been focused on the effects of ingested free radical scavenging polyphenols present in grapes [11,12], rose-hips [13,14], blueberries [15,16], and pomegranates [17][18][19] on oxidative stress markers in animals and humans. The major bioactive compounds within these fruits are besides polyphenols, ascorbic acid, tocopherol, lycopene, tannins, ß carotene, sugars, amino acids, and essential fatty acids [20].…”
Section: Introductionmentioning
confidence: 99%